MENGUBAH KAWAT LISTRIK MENJADI AKSESORIS CANTIK - Chusna Apriyanti; Dwi Rahayu; Indah Puspitasari; Ridha Kurniasih (IKIP PGRI Bojonegoro, 2017)
This entrepreneurship training was aimed to make accessories from electric wire for STKIP PGRI Pacitan students. The basic idea of conducting this activity was changing the priceless electric wire into a beautiful and valuable jewelry. This activity was held on March 10-14, 2017 at campus STKIP PGRI Pacitan. Thirty eight students followed this activity from various departments. This activity was equivalent to 32 hours. Activities are divided into 4 sessions: 3 sessions for theory and practice, and 1 session equivalent to 18 hours for individual assignment. The theories include the introduction of tools and materials used, tips and tricks in starting a business, looking for good raw materials, as well as effective marketing. While the practice included activities to make various accessories made from electrical wire. Assignment involved new creations from the material that has been prepared and the participants were free to combine it with other materials. The participants were equipped with three basic techniques of electric wire: coiling, weaving/woven and netting. In the last session, the participants were given the evaluation of sustainability and monitoring of trainees. In addition, the best three works receive prizes in the form of pliers/equipment and raw materials to encourage participants to develop techniques that have been obtained in the future.Keyword: entrepreneurship, electric wire, accessories, jewelryÂ ABSTRAKKegiatan ini berupa pelatihan kewirausahaan membuat aksesoris dari kawat listrik bagi mahasiswa STKIP PGRI Pacitan. Ide utama dalam kegiatan ini adalah mengubah barang yang tidak terlalu bernilai seperti kawat listrik, menjadi perhiasan cantik yang bernilai jual tinggi apabila. Kegiatan ini dilaksanakan pada tanggal 10-14 Maret 2017 di kampus STKIP PGRI Pacitan. kegiatan ini diikuti oleh 38 mahasiswa dari berbagai jurusan. Kegiatan ini setara dengan 32 jam. Kegiatan dibagi menjadi 4 sesi, yaitu 3 sesi teori dan praktek selama 18 jam serta 1 sesi untuk penugasan individu selama 14 jam. Sesi teori meliputi pengenalan alat dan bahan yang digunakan, tips dan trik dalam memulai usaha, mencari bahan baku yang baik, serta pemasaran yang efektif. Sedangkan kegiatan praktik meliputi kegiatan membuat berbagai aksesoris yang berbahan dasar kawat listrik. Penugasan meliputi penciptaan kreasi baru dari materi pokok yang sudah disedikan dan para peserta bebas mengkombinasikannya dengan bahan lain. Peserta pelatihan dibekali 3 teknik dasar menganyam kawat listrik, yaitu coiling, weaving/woven dan netting. Selesai kegiatan, diberikan evaluasi keberlanjutan dan pemantauan terhadap peserta pelatihan. Selain itu, karya 3 terbaik mendapatkan hadiah berupa tang/peralatan dan bahan mentah untuk memacu peserta untuk mengembangkan teknik yang telah didapat di kemudian hari.Kata Kunci: kewirausahaan, kawat listrik, aksesoris, perhiasan